The patient perspective: perceptions of the quality of the abortion experience. Issue 6 (December 2018) - Altshuler, Anna L.; Whaley, Natalie S.
Abstract : Purpose of review: Abortion services are essential in sexual and reproductive health and should be held to the same standards as other health services. Patient (or person)-centeredness is a key dimension of healthcare quality that incorporates the perspectives of patients in care provision. The purpose of this review is to summarize studies published in the last year examining women's experiences with abortion care and to describe facilitators and barriers to person-centered care. Recent findings: Considering person-centeredness in abortion care using dimensions of dignity, autonomy, privacy, communication, social support, supportive care and health facility environment allows for critical evaluation of data describing women's experiences with abortion and postabortion services. Review of the available literature shed light on the impact of social stigma, health policy and abortion restrictions on women's abortion experiences. Summary: Considering multiple domains and varied settings, current data suggest abortion services worldwide generally fail to provide person-centered care. Institutions and providers may be limited in their ability to provide patient-centered abortion care because of deeply embedded social stigma, institutional regulations and legal restrictions.